ANALISIS KARAKTERISTIK MARSHALL CAMPURAN AC-WC MENGGUNAKAN FILLER ABU BATU ZEOLIT - Sartan Nento; Rahman Abdul Djau; Nasir Bumulo; Wiwin Dayanti (Universitas Gorontalo, 2021)
Materials that are often used as fillers in the AC-WC asphalt mixture are cement and stone ash, because these materials are often used so that supplies are increasingly expensive. For this reason, it is necessary to have new innovations using other alternative materials as fillers which are still quite abundant and easy to obtain, as well as to determine the effect of zeolite as a filler replacement.This research aims to determine the Marshall characteristics of the ac-wc mixture using zeolite rock ash filler, to determine the optimum asphalt content value in the ac-wc asphalt mixture using zeolite rock ash filler. This study used zeolite rock ash filler with variations of 0% 20% 60% 80% and 100% with an asphalt content of 5.5%.From the results of this study, it was found that all variations 0% 20% 60% 80% and 100% met the test specs according to the 2010 revision III. The addition of zeolite rock ash filler variation is the most optimum at a mixture of 100% filler content from the total weight of the mixture.Material yang sering digunakan sebagai filler pada campuran lapis aspal AC-WC adalah semen dan abu batu, karena material tersebut sering digunakan sehingga persediaannya semakin mahal. Untuk itu, perlu ada inovasi baru menggunakan alternatif bahan lain sebagai filler yang masih cukup banyak persediaannya dan mudah didapatkan, juga untuk mengetahui pengaruh zeolit sebagai penggati filler.Peneletian ini bertujuan untuk mengetahui sifat karakteristik Marshall campuran ac-wc menggunakan filler abu batu zeolit, untuk mengetahui nilai kadar aspal optimum pada campuran aspal ac-wc dengan menggunakan filler abu batu zeolit. Penelitian ini menggunakan filler abu batu zeolit dengan variasi 0% 20% 60% 80% dan 100% dengan kadar aspal 5,5%.Dari hasil penelitian ini didapatkan bahwa semua variasi 0% 20% 60% 80% dan 100% memenuhi spek pengujian sesuai sesuai pada bina marga 2010 refisi III. Kadar penambahan variasi filler abu batu zeolit paling optimum pada campuran kadar 100% filler dari berat total campuran